2020
DOI: 10.3390/ijerph17176334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Graduated Walking Program on the Severity of Obstructive Sleep Apnea Syndrome. A Randomized Clinical Trial

Abstract: Background: Obstructive sleep apnea syndrome (OSAS) is a common disease. The objective of this research was to determine the effectiveness of a graduated walking program in reducing the apnea–hypopnea index number in patients with obstructive sleep apnea syndrome (OSAS). Methods: A randomized controlled clinical trial with a two-arm parallel in three tertiary hospitals was carried out with seventy sedentary patients with moderate to severe OSAS. Twenty-nine subjects in each arm were analyzed by protocol. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A total of 249 publications were excluded after screening titles and abstracts, and the full text of 29 studies that were potentially suitable for inclusion was reviewed. Finally, 9 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] met the eligibility criteria, including 444 patients. The main reasons for exclusion were described in the flowchart, which is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 249 publications were excluded after screening titles and abstracts, and the full text of 29 studies that were potentially suitable for inclusion was reviewed. Finally, 9 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] met the eligibility criteria, including 444 patients. The main reasons for exclusion were described in the flowchart, which is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are summarized in Table 1 , Table 2 and Table 3 . Four studies [ 27 , 28 , 29 , 34 ] had protocols with aerobic exercise, and five studies [ 26 , 30 , 31 , 32 , 33 ] had protocols with aerobic exercise combined with resistance exercise. All the exercise interventions followed the principle of exercise prescription, regardless of the exercise modality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only one study by Cavagnolli et al (52), aimed to distinguish the anti -inflammatory effect of exercise in OSAS from its comorbidities and found C-RP was not significantly different between control and non-obese OSAS group. In a recent clinical trial by Jurado-García et al (53), demonstrated that metabolic profile of obese OSAS patients improved after lowintensity exercise. Therefore, it becomes apparent that exercise acts indirectly through obesity in the amelioration of the systemic inflammatory environment.…”
Section: Insulin -Resistant Syndromes and Pro-inflammatory Pronenessmentioning
confidence: 99%
“…Exercise improves the quality of sleep in healthy adults with sleep problems 11 and may reduce obstructive apneas during sleep 12 . Other works showed how exercise may increase sleep duration 13 , e ciency, as well as sleep-associated breathing disorders 14 in patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%